1982
DOI: 10.21273/hortsci.17.5.748
|View full text |Cite
|
Sign up to set email alerts
|

Self-incompatibility Alleles in Broccoli1

Abstract: Seven self-incompatibility (S) alleles (S2, S13, S15, S18, S24, S39, and S51) were identified in various hybrids and breeding lines of broccoli [Brassica oleracea L. (Botrytis group)]. The international S. allele collection of Brassica oleracea at the National Vegetable Research Station was used to assure standardized identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Information on 40 S haplotypes is listed in the study by Ockendon (2000) . From 1975 onwards, Ockendon’s group continued to search S haplotypes in B. oleracea crops, such as broccoli, cabbage, and wild forms ( Ockendon 1980 , 1982 , Stern et al 1982 ), and newly identified and added 10 S haplotypes to the list, resulting in 50 S haplotypes ( Ockendon 2000 ). These S -tester lines were transferred to Dr. Nishio’s group in Tohoku University, Japan.…”
Section: Collection and Unification Of S Haplotypesmentioning
confidence: 99%
“…Information on 40 S haplotypes is listed in the study by Ockendon (2000) . From 1975 onwards, Ockendon’s group continued to search S haplotypes in B. oleracea crops, such as broccoli, cabbage, and wild forms ( Ockendon 1980 , 1982 , Stern et al 1982 ), and newly identified and added 10 S haplotypes to the list, resulting in 50 S haplotypes ( Ockendon 2000 ). These S -tester lines were transferred to Dr. Nishio’s group in Tohoku University, Japan.…”
Section: Collection and Unification Of S Haplotypesmentioning
confidence: 99%